Characteristics of Golden‐winged Warbler territories in plant communities associated with regenerating forest and abandoned agricultural fields. Issue 2 (6th May 2017) - Leuenberger, Wendy; McNeil, Darin J.; Cohen, Jonathan; Larkin, Jeffery L.
Abstract: In the Appalachian portion of their breeding range, Golden‐winged Warblers ( Vermivora chrysoptera ) nest in shrubland and regenerating forest communities created and maintained by disturbance. Because populations of Golden‐winged Warblers have exhibited precipitous declines in population throughout their Appalachian breeding range, management activities that create or maintain early successional habitat are a priority for many natural resource agencies and their conservation partners. Within these early successional habitats, however, additional information is still needed concerning the relative importance of different vegetation features in selection of breeding territories by Golden‐winged Warblers. Our objective, therefore, was to use logistic regression to estimate the probability of territory‐level occupancy by Golden‐winged Warblers in north‐central Pennsylvania at two sites, each with its own early successional community, based on vegetation characteristics. Our communities were composed of shrublands and regenerating forest sites resulting from two disturbances: agriculture and forest fire. Despite differences in vegetation structure, portions of both study areas (regenerating forest and old field) supported territorial Golden‐winged Warblers. Probability of territory occupancy by Golden‐winged Warblers increased with percent blackberry ( Rubus ) cover in the regenerating forest community, and decreased as basal area and distance to microedge increased (i.e., as vegetation patchiness decreased) in both communities. These habitat features have also been found to influence other aspects of Golden‐winged Warbler breeding ecology such as nest‐site selection, pairing success, and territory abundance. Vegetation features influencing Golden‐winged Warbler territory establishment can differ among shrubland and regenerating forest communities, and management decisions and outcomes may be affected by these differences. Our study provides a starting point for a more comprehensive hypothesis‐driven occupancy survey to investigate features of the territories of Golden‐winged Warblers across a broader geographic range and in different vegetation communities.